Challenges in Adherence to Magnetic Resonance Imaging Consensus Recommendations in Multiple Sclerosis: A Call for Improved Neurologist-Neuroradiologist Collaboration - Mafalda Soares; David Berhanu (Acta Médica Portuguesa)
The consensus on MRI in multiple sclerosis Despite major treatment advances in multiple sclerosis (MS), neurologists still face some challenges: the delay in diagnosis and the monitoring of disease progression. Magnetic resonance imaging (MRI) plays an essential role in the clinical management of MS, aiding in the diagnosis, monitoring disease activity, and assessing treatment effects. In 2018 and 2020, the MS Study Group and the Portuguese Society of Neuroradiology published comprehensive guidelines for the use of MRI in MS, detailing the crucial information that neurologists should provide when requesting MRIs (part 1), as well as the suggested MRI acquisition protocols and the structure and content of neuroimaging reports from neuroradiologists (part 2).1,2